Substitution of Tempeh Flour with Beetroot Flour (Beta vulgaris L) in Cookies as Alternative High Protein Snack - Oktavina Permatasari; Arwin Muhlishoh; Zuhria Ismawanti; Adhi Wardhana (Amerta Nutrition, 2022)
Background: Tempeh is a fermented soybean product which high in protein, that beetroot also contains protein and antioxidant compounds. The substitution of tempeh flour and beetroot flour for the cookies can increase the protein nutritional value in cookies. Objectives: This research was to determine the nutrition value of the selected formulation cookies (F1) based on the result of acceptability test of cookies substitution with of tempeh flour and beetroot flour which compared with the SNI standard for supplementary feeding (MP-ASI biscuits). Methods: This is an experimental research with completely randomized design (CRD) with 2 treatment for cookies F1 (substitution of 0.09% tempeh flour and 10% beetroot flour) and cookies F0 (without substitution tempeh flour and beetroot flour). Parameter observed were the nutritional value of cookies are protein, carbohydrate, fat, fiber, water value, and ash value with 3 repetitions. The result of the analysis will be compared the SNI standard for MP-ASI biscuits. Results: From the results of the analysis of the nutrition value of the F1 cookies, that the protein value 12.19%, carbohydrate value 69.19%, fat value 22.73%, fiber value 11.15%, water value 2.96%, and the ash value 2.25% according to SNI requirements for MP-ASI biscuits with protein value of not less than 6 grams per 100 grams. There is a significant difference in protein nutrition value between F0 cookies and F1 cookies. Conclusions: Cookies F1 has protein value, water value, ash value according to SNI standard while charbohydrate and fat value exceeds SNI standard. One serving (2 pieces of cookies equivalent to 20 grams) can meet 9 - 16% of protein needs in toddler 1 - 5 years.